(untitled) (Medical Forum Monthly, 2024)
Objective: To find the accuracy of ultrasound in the predication of birth weight. Study Design: Cross sectional study. Place and Duration of Study: This study was conducted at the Obstetrics, & Gynecology Department, the Lady Reading Hospital Peshawar & Jinnah Medical College Peshawar from 1.7.2012 to 31.12.2012. Materials and Methods: All singleton pregnancies at term (37-42 weeks) with age group 15 to 45 years, attended OPD were enrolled in the study. Informed consent was taken from those participants who meets the inclusion criteria. After detailed history and clinical examination of all pregnant patients were subjected to standard obstetric ultrasound to predict fetal weight. Ultrasound EFW was obtained of all registered pregnant women’s. Had lock reference tables was used for calculating diameter, abdominal circumference and femur length. Birth weight of the neonate was measured with a standard weighing machine to confirm the accuracy of the ultrasound findings. Accuracy of Ultrasound (US) was determined in terms of birth weight of the neonate. The US was considered accurate if the birth weight of the baby lies within ± 200 grams of the estimated fetal weight on US. Results: A total of 159 of women with singleton pregnancies at term (diagnosed by Ultrasound), participated in this study. Mean age of patients was 29.70±5.680 SD years. Mean period of gestation at the presentation was 38 weeks with ±0.887 SD. Fetal weight calculated by ultrasound ranged from 2.50 to 4.30 gram while mean fetal weight was 3.40 gram ±0.401 SD. Actual birth weight ranged from 2.20 to 4.50 gram with mean birth weight of 3.21 ± 0.427 SD. In the study Ultrasound EFW was accurate only in 59 (37.1%) cases i.e. only in 59 cases (37.1%) The estimate weight was ± 200gram of actual weight. while 100 out of 159 estimates (62.9%) were more than ± 200 gram from the actual weight. The over-estimated birth weight was found in 44% (70) by 307grams. Fetal ultrasound underestimated the birth weight in 18.9% (30) of the cases. Fetal ultrasound underestimated the birth weight by 195 grams. The mean error in the estimation of birth weight was 251 grams. Conclusion: A significant error in EFW was found that is 250 grams of actual weight. Therefore depending on only ultrasound for EFW may lead obstetrical interventions.